International security regimes in preventing the spread of nuclear armaments and their global significance - Ilić, Srećko D.; Radovanović, Radovan V.; Ivković, Aleksandar S. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The paper provides an overview of international regimes and agreements that aimed to halt the spread of nuclear weapons. For each regime, its impact on nuclear weapons proliferation is presented, as well as its significance in stopping nuclear tests that posed a threat of a global ecological catastrophe. Many of these regimes are no longer in effect today, but throughout history, they played their role in fulfilling specific needs to halt the global spread of nuclear weapons or characteristic nuclear weapons of a certain range. Methods: The paper analyses the international agreements in this field, as well as the papers in the field of nuclear safety from journals of international importance. Results: The analysis of nuclear security regimes gave results that speak of their strengths and weaknesses. The importance and weaknesses of the regimes are given through the analysis and several diagrams that show the trend of increasing the amount of nuclear weapons over time.Conclusions: The work points to the historical importance of nuclear security regimes, but also to their weaknesses, both in earlier times and today. It is clear that these regimes halted nuclear weapons, but this halt did not lead to the complete abolition of nuclear weapons, which is the ultimate goal of the agreements.
Keywords: security regimes; nuclear weapons; proliferation; nuclear tests; international agreements